The Influence of Fiber Processing and Alkaline Treatment on the Properties of Natural Fiber-reinforced Composites: A Review - Setswalo, Keagisitswe; Molaletsa, Namoshe; Oladijo, Oluseyi Philip; Akinlabi, Esther Titilayo; Rangappa, Sanjay Mavinkere; Siengchin, Suchart (Applied Science and Engineering Progress, 2021)
Throughout generations, research on natural fiber-reinforced composites (NFRCs) has been growing and yielding promising results. The notion of blending natural fibers with polymers comes from the composite’s suitable properties, not limited to low density, availability at a low price, biodegradability, and environmental friendliness. The quest for high-performing and marketable NFRCs is driving innovation in the synthesis of such materials. A suitable combination of parameters that optimizes the mechanical and functional properties of the composites without increasing the cost of production is desired. The main objective of this review is to evaluate some of the parameters that influence the behavior and properties of NFRCs. The influence of alkaline modification and natural fiber processing parameters, such as particle size, modification concentration, soaking duration, processing temperature, fiber-to-polymer ratio, and adoption of additives, on composites are discussed. This review summarizes some of the work and provides some directions in the search of an all-around performing economic NFRC.